2015
DOI: 10.1002/stem.2056
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Quiescence in Adult Stem Cells: Biological Significance and Relevance to Tissue Regeneration

Abstract: Adult stem cells (ASCs) are tissue resident stem cells responsible for tissue homeostasis and regeneration following injury. In uninjured tissues, ASCs exist in a nonproliferating, reversibly cell cycle-arrested state known as quiescence or G0. A key function of the quiescent state is to preserve stemness in ASCs by preventing precocious differentiation, and thus maintaining a pool of undifferentiated ASCs. Recent evidences suggest that quiescence is an actively maintained state and that excessive or defective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
124
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(133 citation statements)
references
References 98 publications
2
124
0
1
Order By: Relevance
“…The reactivation of qNSCs into proliferation is crucial for tissue repair and regeneration. This reactivation not only exists in neural stem cells, but it also occurs in other tissue stem cells such as fibroblasts and hematopoietic stem cells (Rumman et al, 2015). Studies in the past few years have revealed that, instead of being a passive state, quiescence is actively maintained in the cell (Spencer et al, 2013; Hilpert et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The reactivation of qNSCs into proliferation is crucial for tissue repair and regeneration. This reactivation not only exists in neural stem cells, but it also occurs in other tissue stem cells such as fibroblasts and hematopoietic stem cells (Rumman et al, 2015). Studies in the past few years have revealed that, instead of being a passive state, quiescence is actively maintained in the cell (Spencer et al, 2013; Hilpert et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…MuSCs are quiescent (G 0 phase) during homeostasis (Rumman et al, 2015;Schultz et al, 1978). Following injury, they re-enter the cell cycle, proliferate to give rise to myoblasts that differentiate and fuse to restore the damaged fibre or generate myofibres de novo (Moss and Leblond, 1970;Reznik, 1969;Snow, 1977).…”
Section: Morel Et Al 2007)mentioning
confidence: 99%
“…Cumulative studies have shown that maintenance of SC quiescence in a number of SCs such as hematopoietic SCs, muscle satellite cells, and skeletal mesenchymal SCs is clinically relevant for enhancing tissue regeneration. 7 …”
Section: Introductionmentioning
confidence: 99%